Ultrathin perfect absorber based on integrated metamaterial - Lam, Tran Tien; Nga, Dinh Thi; Thien, Dinh Van; Khiem, Nguyen Sy; Khuyen, Bui Xuan; Tung, Bui Son; Lam, Vu Dinh (Vietnam Journal of Science and Technology, 2020)
We improved common metamaterial perfect absorber (MPA) by integrating four embedded inductors or replacing four embedded capacitors in the same compact structure. The obtained results confirmed that the lumped-capacitors MPA maintains an extreme thickness t = λ/940, where λ is operating wavelength at 106.3 MHz. Besides, by replacing these capacitors by inductors in the initial designed-MPA structure, we obtained an effective thickness of t = λ/53 at 1.9 GHz. Furthermore, we explained the absorption mechanism in terms of the magnetic energy and power loss distributions related to the impedance-matching effect.